If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 8) = 13 Reorder the terms: 3(8 + 5x) = 13 (8 * 3 + 5x * 3) = 13 (24 + 15x) = 13 Solving 24 + 15x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 15x = 13 + -24 Combine like terms: 24 + -24 = 0 0 + 15x = 13 + -24 15x = 13 + -24 Combine like terms: 13 + -24 = -11 15x = -11 Divide each side by '15'. x = -0.7333333333 Simplifying x = -0.7333333333
| 11/2c=6 | | x+(x+6)=58 | | -25y+-55= | | 30-2k=20 | | -12x-6=0 | | F(x)=cos(9x) | | 2a-10=9a+11 | | 3(2x-5)27= | | 3(X-2)+5=2(5x+4) | | 136-4x= | | -2x+12-4x= | | 3+2g=7-6g | | 3^2=1/81 | | 13x+8=5x | | 2.4c=48 | | f(x)=3x^2-363 | | (x-1)-x(3x-2)=0 | | x+3y=600 | | 0.5x^2+1.5x-54=0 | | x+(n+80)=400 | | y=8sin(x)+15 | | 3y-6x=8 | | 3x+x=4200 | | 16-n+35=42 | | x^2+2x+2=2x^2+2x | | 3S+4=-6 | | 12x^2-10=48 | | S=1.06-0.325s | | X=5+-0.25x | | 26+17-n=28 | | 3/h=9/3h | | 10x+5+12x-1=90 |